Comparative analysis of soil properties before and after Morchella sextelata cultivation across various soil types - Zhao, Juan; Zeng, Rui; Zhang, Chengming; He, Bin; Zhang, Qin; Zhou, Qihong; Gong, Zikang; Liu, Honglin; Liu, Songqing (Frontiers in Microbiology, 2025)
Morchella, a highly nutritious edible fungus, has been successfully cultivated through artificial means. However, as cultivation areas have expanded, declining yield have emerged more prominently. Soil physicochemical characteristics and microbial communities were critical to production on cultivating morels. In this study, our results reveals that cultivation significantly alters soil properties and microbial communities in a soil type-dependent manner. In sandy soil, pH and key nutrients (total nitrogen, total phosphorus, available phosphorus) increased, while potassium and calcium levels decreased. Microbial diversity decreased in sandy soil but increased in paddy soil, with the overall community structure in sandy soil being more drastically reshaped. Metagenomic profiling identified distinct differential taxa and functional shifts, showing that sandy soil exhibited greater enrichment of microbial genes, including soil-borne diseases. These findings demonstrate that M. sextelata cultivation induces considerable and contrasting changes in soil nutrient profiles and microbiome composition, with sandy soil being more susceptible to microbial restructuring and potential pathogen enrichment.